2021
DOI: 10.1016/j.bios.2020.112747
|View full text |Cite
|
Sign up to set email alerts
|

Long period grating in double cladding fiber coated with graphene oxide as high-performance optical platform for biosensing

Abstract: In this work, the development and testing of a novel fiber-optic based label-free biosensor is presented, whose performance were verified through the detection of C-reactive protein (CRP) in serum. The device is based on a long period grating fabricated in a double cladding fiber with a W-shaped refractive index (RI) profile. As a result, the working point of the device was tuned to the mode transition region by chemical etching of the outer fiber cladding, obtaining a significant enhancement of the RI sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Thus, it is concluded that a λ D deviation induced by ambient temperature changes rarely affects the measurement accuracy of our antigen detection experiments carried out at room temperature, because the Δ λ D , det value of ∼0.0109, obtained by a λ D deviation of 0.01 nm, is close to the Δ λ D , det magnitude obtained in the bare PS-LPFG. For further implementation of a completely temperature-insensitive system, it is necessary to include a temperature control system based on thermo-electric cooling devices such as Peltier elements in our sensor system [ 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is concluded that a λ D deviation induced by ambient temperature changes rarely affects the measurement accuracy of our antigen detection experiments carried out at room temperature, because the Δ λ D , det value of ∼0.0109, obtained by a λ D deviation of 0.01 nm, is close to the Δ λ D , det magnitude obtained in the bare PS-LPFG. For further implementation of a completely temperature-insensitive system, it is necessary to include a temperature control system based on thermo-electric cooling devices such as Peltier elements in our sensor system [ 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Among carbon-based materials, graphene-oxide (GO) is widely used to coat optical fibers with the purpose of developing immunosensors with enhanced sensitivity. The structure of this material consists in a 2D honeycomb lattice with carbon atoms, containing functional groups such as hydroxyl, epoxy and carboxyl on its basal plane and sheet edges [ 111 ]. As a result, GO can covalently bind to antibodies due to the abundant presence of functional groups on its surface [ 97 ].…”
Section: Biofunctionalization Strategies For Optical Fiber Immunosensorsmentioning
confidence: 99%
“…These values are at least 20 times higher than the ones presented in [ 118 ]. In this context, further improvements have been achieved when gratings were inscribed in etched cladding fibers [ 122 ] and/or fibers were coated with thin films [ 79 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. L. Coelho et al at INESC TEC conducted relevant research related to the influence of metal oxide coating on arc-induced gratings and their applications as refractometric sensors [ 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ].…”
Section: Lpfgs’ Sensitivity To Fabrication and Physical Parametersmentioning
confidence: 99%
“…Long period fiber gratings are very sensitive to changes in physical parameters, such as, temperature [ 51 ], strain [ 52 , 53 ], transverse load [ 54 ], bending [ 55 ], torsion [ 56 ] and refractive index of the surrounding medium [ 57 , 58 , 59 ] and, therefore, several sensor heads have been proposed to monitor temperature in extreme environments [ 60 , 61 ], structural integrity [ 62 ], multi-directional bending [ 63 ] and torsion [ 64 ]. On the other hand, coated LPFGs [ 65 , 66 , 67 ] can act as refractometric sensors [ 68 , 69 ] able to monitor an enormous quantity of physical [ 70 , 71 , 72 ], chemical [ 73 , 74 , 75 ] and biological parameters [ 76 , 77 , 78 , 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%